The Importance of Open Access, Open Source, and Open Standards for Libraries - Edward M. Corrado (Issues in Science and Technology Librarianship)
The open access, open source software, and open standards concepts have been garnering increased attention in the field of librarianship and elsewhere. These concepts and their benefits and importance to libraries are examined. Benefits include lower costs, greater accessibility, and better prospects for long-term preservation of scholarly works. [ABSTRACT FROM AUTHOR]